The economic of deterrence: a wrong policy or a misplaced strategy? - Evan Lau,; Siti Nur Zahara Hamzah,; Muzafar Shah Habibullah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper investigates the impact of economics conditions and deterrence variables on disaggregated crime data in Sarawak, using yearly time-series data spanning more than 40 years using a vector error correction estimates. It is proven that economic variables studied serve as motivation of crime in Sarawak and imprisonment does not deter crime in the time period studied. It is evident that imprisonment in the case of Sarawak is less influential in deterring crime or the society were ill informed of the severity of punishment. While the study established a long-run relationship between economics and crime, it is also a noble approach in understanding deterrence in the context of Sarawak. Both economics and deterrence variables are important in explaining the decline in crime and in formulating efficient strategy and policies to combat crime. Government should shift the focus of increasing number of police force to increasing awareness on severity of punishments. At the same time, increasing opportunity for legal jobs would be important to deter crime.